Sons and parental cognition in mid-life and older adulthood - Wolfova, Katrin; Wu, Di; Weiss, Jordan; Cermakova, Pavla; Kohler, Hans-Peter; Skirbekk, Vegard Fykse; Stern, Yaakov; Gemmill, Alison; Tom, Sarah E (Journal of psychiatric research, 2022)
Prior research suggests a relationship between number of sons and maternal long-term health outcomes, including dementia. We assessed the relationship between having sons and parental cognitive aging. Specifically, we investigated the relationship between having at least 1 son and parental baseline cognition level and rate of cognitive decline, accounting for life course sociodemographic characteristics in a cohort of 13 222 adults aged ≥50 years from the US Health and Retirement Study. We included only participants with at least one child. We further explored whether this relationship varies by parental sex and whether the magnitude of the relationship increases with each additional son. Cognition was assessed biennially for a maximum of nine times as a sum of scores from immediate and delayed 10-noun free recall tests, a serial 7s subtraction test, and a backwards counting test. Associations were evaluated using linear mixed-effects models, stepwise adjusting for sociodemographic and health-related factors. In our analytic sample of parents, a total of 82.3% of respondents had at least 1 son and 61.6% of respondents were female. Parents of at least 1 son had a faster rate of cognitive decline in comparison to parents without any son. Our results also suggest that cognitive decline was faster among parents of multiple sons, compared to parents with only daughters. Thus, the results support the theory that having sons might have a long-term negative effect on parental cognition.
Keywords: Family; Parents; Child; lidé; Female; senioři; mužské pohlaví; rodina; Male; dítě; Health and retirement study; Aged; Offspring sex; rodiče; Cognitive aging; ženské pohlaví; Humans